How the Sodium Cations in Anode Affect the Performance of a Lithium-ion Battery - Dan Shao; Dewei Rao; Aihua Wu; Xiangyi Luo (Batteries, 2022)
Large cations such as potassium ion (K+) and sodium ion (Na+) could be introduced into the lithium-ion (Li-ion) battery system during material synthesis or battery assembly. However, the effect of these cations on charge storage or electrochemical performance has not been fully understood. In this study, sodium ion was taken as an example and introduced into the lithium titanium oxide (LTO) anode through the carboxymethyl cellulose (CMC) binder. After the charge/discharge cycles, these ions doped into the LTO lattice and improved both the lithium-ion diffusivity and the electronic conductivity of the anode. The sodium ion’s high concentration (>12.9%), however, resulted in internal doping of Na+ into the LTO lattice, which retarded the transfer of lithium ions due to repulsion and physical blocking. The systematic study presented here shows that large cations with an appropriate concentration in the electrode would be beneficial to the electrochemical performance of the Li-ion battery.